Factors Associated With and Characteristic of HIV/Tuberculosis Co-Infection: A Retrospective Analysis of SECOND-LINE Clinical Trial Participants. (1st May 2021) - Henry, Rebecca T.; Jiamsakul, Awachana; Law, Matthew; Losso, Marcelo; Kamarulzaman, Adeeba; Phanuphak, Praphan; Kumarasamy, Nagalingeswaran; Foulkes, Sharne; Mohapi, Lerato; Nwizu, Chidi; Wood, Robin; Kelleher, Anthony; et al.
Abstract : Background: Tuberculosis (TB) is a common infection in people living with HIV. However, the risk factors for HIV/TB co-infection in second-line HIV therapy are poorly understood. We aimed to determine the incidence and risk factors for TB co-infection in SECOND-LINE, an international randomized clinical trial of second-line HIV therapy. Methods: We did a cohort analysis of TB cases in SECOND-LINE. TB cases included any clinical or laboratory-confirmed diagnoses and/or commencement of treatment for TB after randomization. Baseline factors associated with TB were analyzed using Cox regression stratified by site. Results: TB cases occurred at sites in Argentina, India, Malaysia, Nigeria, South Africa, and Thailand, in a cohort of 355 of the 541 SECOND-LINE participants. Overall, 20 cases of TB occurred, an incidence rate of 3.4 per 100 person-years (95% CI: 2.1 to 5.1). Increased TB risk was associated with a low CD4 + -cell count (⩽200 cells/μL), high viral load (>200 copies/mL), low platelet count (<150 ×10 9 /L), and low total serum cholesterol (⩽4.5 mmol/L) at baseline. An increased risk of death was associated with TB, adjusted for CD4, platelets, and cholesterol. A low CD4 + -cell count was significantly associated with incident TB, mortality, other AIDS diagnoses, and virologic failure. Discussion: The risk of TB remains elevated in PLHIV in the setting of second-line HIV therapy in TB endemic regions. TB was associated with a greater risk of death. Finding that low CD4 + T-cell count was significantly associated with poor outcomes in this population supports the value of CD4 + monitoring in HIV clinical management.